Beguiling voices: traces of vocality in the Malay literary tradition of the Riau islands. Issue 1 (2nd January 2017) - McCallum, Jenny
ABSTRACT: What can we learn about the history of Malay sounding traditions? With no musical notation, treatises or recordings to draw on, I turn to traditional literary adventures from island Riau (present-day Indonesia). This article re-imagines what has long been understood as a literary tradition as a sounding one, recalling that manuscripts were recited rather than read silently and that the stories themselves are rich sources on music and sound, in particular sounding voices. I focus on the particular power of voices in these texts to beguile, persuade and effect plot development, and analyse the vocabulary used to describe such voices. Finally, the article considers how external influences on the world of Malay sounding voices contributed to their separation from the written literary tradition and the eventual decline in popularity of recitation practices. This research seeks to contribute to the theorisation of vocality and to highlight its cultural and historical specificity, including its relation to the colonial encounter.